An Unusual Presentation of Recurrent Childhood Kimura Disease: Ileocecal Involvement. Issue 5 (July 2021) - Ranjith Kumar, Venkataraman; Ramamoorthy, Jaikumar G.; Basu, Debdatta; Arumugom, Archana; Jose, Divakar; Cherian, Anchu A.
Abstract : Kimura disease commonly presents as an isolated swelling over the head and neck region. Intestinal involvement by Kimura disease in children is uncommonly reported. We report a 10-year-old boy who had presented with an ileocaecal mass with peripheral blood eosinophilia and elevated immunoglobulin E levels. The histopathologic examination from the ileocaecal mass was suggestive of Kimura disease. He had 2 recurrences once in the left axillary region and once in the bilateral cervical region. Ileocaecal involvement in Kimura disease is an uncommon presentation in childhood. Careful evaluation of complete blood count is critical in making diagnosis and avoiding unnecessary invasive procedures.